Sonographic variations in common bile duct dimensions - Joshi, B. Raj (Journal of Institute of Medicine Nepal, 2010)
Introduction: Biliary diseases such as cholelithiasis, cholecystitis, hepatitis, cirrhosis and pancreatitis are common in Nepal. Cholelithiasis was present in 8 percent of the emergency patients, second to acute appendicitis. Acute cholecysistitis was present in 25 percent of these patients. 1 The most common operation in a district hospital was cholecystectomy (31%]). 2 Ultrasound plays an integral part in evaluation of biliary system. The aim of the study was also to determine whether the size of the CBD increases with age. Methods: We prospectively collected data on 100 patients aged 15 years or older who underwent abdominal sonography. The subjects had no history of biliary and pancreatic disease or operation. The CBD was measured in porta hepatis, in the distal aspect of head of pancreas and midway between these points. Linear regression was used to correlate age with the dimension. Results: There were 30 males and 70 females in the study. The subjects ranged from 15 to 80 years. The mean diameters were as follows: 3.76mm in proximal, 4.26 mm in middle, 4.90mm in distal portion of CBD. The overall measurement was 4.23mm. Conclusions: There was a significant correlation between CBD size and age. Correlation with age was best observed for the distal segment. Keywords: Biliary diseases, CBD, ultrasound. DOI: 10.3126/joim.v31i3.2993 Journal of Institute of Medicine, December, 2009; 31(3) 27-29